Pengaruh Literasi Pajak dan Digitalisasi Terhadap Kepatuhan Wajib Pajak UMKM: Studi Kasus UMKM di Kabupaten Tangerang - Hindayani, Novia; Arum, Mega (JAB (Jurnal Akuntansi & Bisnis), 2025)
Digitalization has transformed tax administration by enhancing the ability to collect, process, and monitor tax information more quickly and accurately. Indonesia has also adopted tax digitalization. The Indonesian government, through the Directorate General of Taxes (DGT), has begun implementing a more digital tax system to help Micro, Small, and Medium Enterprises (MSMEs) comply with their tax obligations more easily. This study aims to analyze the influence of tax literacy and digitalization on MSME taxpayer compliance. Data were collected through a survey of 99 respondents consisting of MSME actors across various business sectors. Descriptive analysis shows that most respondents are aged between 26–35 years (56.6%), with the majority being female (58.6%). The culinary sector dominates with a contribution of 38.4%. Validity tests indicate that all items within the variables of tax literacy, digitalization, and taxpayer compliance are valid, with Pearson Correlation values exceeding 0.1975. Reliability testing also shows strong results, with Cronbach’s alpha values above 0.70. Multiple linear regression analysis was used to examine the effect of tax literacy and digitalization on taxpayer compliance. The results show that both variables have a positive and significant impact on taxpayer compliance. Tax literacy has a regression coefficient of 0.462 (p < 0.05), while digitalization has a coefficient of 0.192 (p < 0.05). The coefficient of determination (R²) of 0.769 indicates that 76.9% of the variation in taxpayer compliance can be explained by tax literacy and digitalization, with the remaining 23.1% explained by other variables outside the scope of this study. The F-test results confirm that tax literacy and digitalization simultaneously have a significant influence on taxpayer compliance (p < 0.05). This study highlights the importance of enhancing tax literacy and embracing digitalization as strategic measures to improve MSME taxpayer compliance.